Peran K.H. A. Muhammad Isa pada Tahun 1989-2021 dalam Perwujudan Islam Moderat di Cianjur Selatan - Alwan Alwan; Mahrus As'ad; Muhammad Riza (UIN Sunan Gunung Djati Bandung, 2021)
K.H. A. Muhammad Isa was very instrumental in spreading the teachings of moderate Islam in South Cianjur. Practically, he took moderate steps as the best effort to address the differences in views between the conservative and modernist camps in responding to the changing times. He was very instrumental in translating the syarah texts of Arabic books, making them easy to understand and widespread among the Ulama of Cianjur Regency. He is also a Falak Ulama and a member of the Hisab and Rukyat Agency the Ministry Religion of the Republic Indonesia, thus making him always involved with the Ministry Religion of the Republic Indonesia in determining the new moon and one Shawwal. This paper tries to reveal the progress of K.H. A. Muhammad Isa in the Embodiment of moderate Islam in South Cianjur. To obtain valid data, the method used in this research is a historical research method, which is a systematic procedure or technique with the principles and rules of History. The technique in question includes several steps, including: selection of sources (heuristics), internal and external criticism (verification), data analysis and interpretation (interpretation), and presentation in written form (historiography). With this paper, future generations of Muslims are expected to be able to take role models from the figures discussed and be able to represent the attitude of religious moderation as a pillar of national integration; the creation of a tolerant and harmonious religious life so as not to cause national disintegration.